2002
DOI: 10.1016/s1631-0748(02)01454-6
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of zinc sodium polyphosphates glasses from coacervates precursors. Characterisation of the obtained glasses, and their applications

Abstract: A soft chemistry route is described to obtain glasses in the P 2 O 5 -Na 2 O-ZnO-H 2 O. It is based on the addition of zinc salts to coacervates prepared from sodium polyphosphate. The processing of these coacervates leads to polyphosphate glasses with the same properties as those of glasses prepared in the classical way. So far, little work has been implemented in this system using 'coacervate route'. However, it makes an attractive method for coating and joining processes on the industrial scale. As the anio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 19 publications
0
17
0
2
Order By: Relevance
“…The chelation of divalent cations by polyphosphate chains caused the pH of the solution to decrease, an effect previously reported by several researchers. 21,31,32 We showed that the pK a value of hydrogen atoms at the end of the chains also decreases during chelation. This pH effect can be explained, therefore, by the dissociation of hydrogen atoms at the chain ends.…”
Section: Discussionmentioning
confidence: 85%
“…The chelation of divalent cations by polyphosphate chains caused the pH of the solution to decrease, an effect previously reported by several researchers. 21,31,32 We showed that the pK a value of hydrogen atoms at the end of the chains also decreases during chelation. This pH effect can be explained, therefore, by the dissociation of hydrogen atoms at the chain ends.…”
Section: Discussionmentioning
confidence: 85%
“…In this paper, our methodology was based on the work proposed by Umegaki et al [1]. These authors suggested that after the addition of methanol to sodium polyphosphate solution a liquidliquid phase separation occurs, considering the coacervate obtained as the denser phase [12,14]. In this paper, we studied the synthesis of sodium coacervates and how the addition of different amounts of methanol (4.25…”
Section: Coacervate Characterizationmentioning
confidence: 99%
“…The addition of solvents, such as alcohols or acetone to aqueous sodium polyphosphate, in order to prepare coacervates is known through literature. However, in some cases, the addition of divalent cations occurs, as Zn 2þ , Co þ , Ni 2þ etc., for example, [5,12,14]. The novelty in this work is that the coacervation occurs by adding methanol to the polyphosphate without needing the presence of another cation.…”
Section: Coacervate Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have previously confirmed the osteoconductivity, biocompatibility and degradable nature of CPP [5e13] and it has been studied for use in cartilage and bone repair, as well as for angiogenesis [9,14e18]. In the literature, CPP is most commonly fabricated in the furnace [6,19]. Unfortunately, only a few studies have examined the chain length of this "melt-derived" CPP as a function of furnace conditions and the results have proven inconclusive [20e22].…”
Section: Introductionmentioning
confidence: 99%